Colonial Museum of Luanda, 1907-1910: Support for Reproduction and Apologetics of the Imperial Sovereignty (Cadernos de Sociomuseologia, 2018)
This study aims to reflect, with the advisable national and international contextualization, upon the Colonial Museum of Luanda, 1907/1910 - an attempt of symbolic Power leading to the Reproduction and Apologetics of the Empire, at the time of the so called African Empire – legitimized by the visit of Prince Royal Luis Filipe, Duke of Braganza, in 1907, during the Imperial Tour that took him from the Tagus River to the Atlantic and Indian Oceans, with return trip, 100 years after the departure of his great-grandparents bound for Brazil.This Colonial Museum is seen in this study as a symbolic representation of the Colonial Political Power and the Imperial Political Power in the sum of the various collections exhibited inside, on the balconies and the surrounding spaces of the Magnetic and Meteorological Observatory; the edition of the corresponding catalogue, Catálogo do Mostruário de Produtos da Província de Angola; the collection of photographs of the time, in a glass support, the so-called "glass plates"; the representative portrait of the King, who, despite being absent, is present; the Visit and the rallying Words of the Prince Royal, accompanied by his royal court; the ennobling architecture of the Museum, a reutilization of an old temple with a high Bell Tower; and the site of the Museum itself, as a whole, in the upper part of the city - a centre of Power.As its organizer, emphasis is given to the Director of this Observatory, Ernesto Augusto Gomes de Souza, Frigate Captain, Aide-de-camp of King Charles I and King Manuel II, and occasional Acting Governor-General of Angola, among other functions.The museological collections, in part unprecedented, here reflected upon, were understood, in the past, as having been illustrative of the appeal of the symbolic appropriation of the Other and its richness; these collections, today "reinstated", are considered, in this study, as potential facilitators of the reconciliation between Peoples of Common Language, whose language is "also ours", the so-called “Language of travel and even miscegenation ", from “where it is possible to observe the Sea”. Keywords: Colonial Museum; Prince Royal Luis Filipe; Imperial Tour; Symbolic Power; Angola.